Makna Harap-Harap Cemas dalam Qasidah Burdah: Kajian Analisis Semiotika (NUMADURA: Journal of Islamic Studies, Social, and Humanities, 2023)
The purpose of this article is to discuss the meanings contained in the Burdah Qasidah, specifically the poem of Al-Bushiri in verses 140-160, based on semiotic analysis. The method used to uncover the meaning of the poem is descriptive qualitative research, which will describe the hopes and anxieties conveyed in the Qasidah Burdah by Al-Bushiri. The object of this research is the verses found in lines 140-160, focusing on the concepts of fear (khouf) and hope (roja'), as well as regrets/worries. The research highlights Al-Bushiri's concept of hope and anxiety based on factual evidence. The results of the research indicate that the term "syi'ri" has a basic meaning of "poetry or poem," but has a relational meaning of sinful speech. On the other hand, the term "khidami" has a basic meaning of "service," but in a relational sense, it carries the meaning of sin caused by actions/body parts. There is also a paradigmatic meaning, where "syi'ri" signifies minor sins and "khidami" signifies major sins. The paradigmatic meaning of Al-Bushiri's poem in verses 140-160 is the phrase "lam tasytari ad diina bi ad dunya" which juxtaposes with "wa man yabiu aajilan minhu bi'ajilihi" and conveys the meaning of selling the hereafter for the worldly gains, buying the world with religious capital.